2021
DOI: 10.1093/rheumatology/keab664
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of fibroblast activation protein in rheumatoid arthritis patients: imaging and ex vivo photodynamic therapy

Abstract: Objective Activated synovial fibroblasts are key effector cells in rheumatoid arthritis (RA). Selectively depleting these based upon their expression of fibroblast activation protein (FAP) is an attractive therapeutic approach. Here we introduce FAP imaging of inflamed joints using [68Ga]Ga-FAPI-04 in an RA patient, and aim to assess feasibility of anti-FAP targeted photodynamic therapy (FAP-tPDT) ex vivo using 28H1-IRDye700DX on RA synovial explants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Some articles focused particularly on the role of FAPI imaging for the assessment of RA in preclinical setting, with the demonstration of the high specificity of this tracer for arthritic joints, both in vitro and in vivo. In this setting, some pilot clinical evaluations for the use of radiolabeled FAPI PET/CT in subjects with RA have also been proposed, suggesting its potential application to visualize arthritic synovium related to the specific upregulation of the expression of FAP in this site [ 10 , 30 , 31 ].…”
mentioning
confidence: 99%
“…Some articles focused particularly on the role of FAPI imaging for the assessment of RA in preclinical setting, with the demonstration of the high specificity of this tracer for arthritic joints, both in vitro and in vivo. In this setting, some pilot clinical evaluations for the use of radiolabeled FAPI PET/CT in subjects with RA have also been proposed, suggesting its potential application to visualize arthritic synovium related to the specific upregulation of the expression of FAP in this site [ 10 , 30 , 31 ].…”
mentioning
confidence: 99%
“…Unfortunately, phase I/II clinical trials with an anti-FAP monoclonal antibody in cancer treatment did not show meaningful clinical efficacy probably due to the fact that the non-toxic unconjugated monoclonal antibody did not induce cell death ( 48 ). Recently, Dorst et al ( 49 ) conjugated a near infrared dye, IRDye700DX to a monoclonal antibody (28H1) to FAP and demonstrated that in vitro 28H1-700DX was capable of killing FAP expressed fibroblast cell line (3T3) and primary synovial fibroblasts from synovial biopsy of RA patients ( 50 ). Furthermore, 28H1-700DX had moderate effect on development of CIA presumably by inducing death of FAP expressing synovial fibroblasts ( 49 ).…”
Section: Cell Surface Proteins Serve As Targets For Ablation Of Fibro...mentioning
confidence: 99%
“…No reports have shown the utility of FAP targeted imaging in PMR patients to date. Yet, successful FAP targeted imaging has been demonstrated in RA patients which may point to its potential to image inflammation in PMR patients as well ( 369 ).…”
Section: Potential Novel Pet Tracers For Diagnosis and Monitoring Of ...mentioning
confidence: 99%